Pilot Cafe / Abdul Sharfiz Ahmad Zaidi - Ahmad Zaidi, Abdul Sharfiz; Alexson Nicholas Bundan, Lydiana; Senapi, Roziah
Pilot Cafe is determined to become a daily necessity for local coffee addicts and internet addicts, it is a place to dream of as you try to escape the daily stresses of life and just a comfortable place to meet your friends or to read a book, all in one. With the growing demand for high-quality gourmet coffee and great service. Pilot Cafe will capitalize on its proximity to the University of Mara Technology to build a core group of repeat customers. Pilot Cafe will offer its customers the best prepared coffee in the area that will be complimented with pastries, as well as free books and internet service that its patrons can read and surfing to enjoy their visit. Pilot Cafe will provide a unique forum for communication and entertainment trough the medium of the internet. Pilot Cafe like it is the answer to an increasing demand. Pilot cafe provides access to methods of communication, and volume of information now available on the internet to the public. Public also can access at a cost they can afford and in such way that they are not socially, economically, or politically isolated. Pilot Cafe goal is to provide the community with a social, educational, entertaining, atmosphere for worldwide communication. This business plan is prepare to obtain financing in the amount RM500 000, to begin work on site preparation and modification, equipment purchases, and to cover expenses in the first year of operations.